Effect of Atomic-Layer-Deposited Hydroxyapatite Coating on Surface Thrombogenicity of Titanium - Abushahba Faleh; Areid Nagat; Kylmäoja Elina; Holopainen Jani; Ritala Mikko; Hupa Leena; Tuukkanen Juha; Närhi Timo (MDPI, 2025)
This study aimed to evaluate the surface characteristics of a nanocrystalline hydroxyapatite coating made through atomic layer deposition (ALD-HA) on titanium surfaces and to investigate its effect on blood coagulation and platelet adhesion. Grade 2 square titanium discs (0.7 cm, 1 mm thick) were used (n = 108). Half of the substrates (n = 54) were coated with ALD-HA, and the other half were used as the non-coated control. Surface free energy (SFE), contact angle (CA), surface roughness (Ra), and chemical composition were evaluated. Blood thrombogenic properties were assessed on ALD-HA and non-coated surfaces using the kinetic clotting time method. The platelets’ adhesion and morphology were also evaluated. The ALD-HA-coated surfaces demonstrated significantly higher polar SFE (p < 0.001) and lower CA (p < 0.001) values compared to the non-coated surfaces. In addition, the surface roughness was significantly lower for the ALD-HA (p < 0.001) than for the non-coated surfaces. Platelets adhered to both surfaces; however, there was variability in platelet morphologies in different areas with higher platelet density on the ALD-HA surfaces. There was no significant difference in the overall absorbance values of the hemolyzed hemoglobin for both substrates, and the total clotting time was achieved at 60 min. It can be concluded that the ALD-HA coating of titanium can enhance surface wettability, increase surface free energy, and support blood coagulation and platelet adhesion.